UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) PADA PELAJARAN IPA - Mursilah, Mursilah (JURNAL SINEKTIK, 2020)
The purpose of this research was to improve student learning outcomes using the contextual teaching and learning model (CTL), in natural science lessons on the sub-theme of plants as a source of life, design research of Classroom Action Research (CAR), two cycles and four stages each; plans, actions, observations and reflections. The research subject were class VI elementary school number 51/IX Setiris Muaro Jambi, consisting of 22 students. Data collection techniques used observation and formative tests, Data analysis used simple tabulation calculations, the success criteria are ?73 individually and 100% classical, the results showed that, learning success score 18% increased to 64% in the first cycle and increased again to 100% in the second cycle, with the highest score of 84, the lowest score of 73 and an average score of 79.71, teacher observation by 70% increased to 88%, student observation by 65% increased to 85%. Therefore, it can be concluded that the CTL learning model can improve student learning outcomes in natural science on the sub-theme of plants as a source of life in class VI students of elementary school number 51 / IX Setiris Muaro Jambi district.